2019
DOI: 10.1108/jfp-11-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

A multi-site survey of forensic nursing assessment

Abstract: Purpose A major difficulty identified many years ago in psychiatric care is the shortage of appropriate instruments with which to carry out valid and reliable therapeutic assessments which are behaviourally based and therefore appropriate for use in a variety of contexts. The aim of this project was to ascertain the utility of a forensic nursing risk assessment tool - Behavioural Status Index (BEST-Index). The paper aims to discuss these issues. Design/methodology/approach A multi-site cross-sectional survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…Less in known about change at a proximal level, thus change in risk relevant behavior during treatment while behavioral change is an important precondition for violence risk prediction. Moreover, assessment of risk relevant behavior is an ongoing process that forensic staff in general but psychiatric nurses in particular undertake on a daily basis (Walker et al, 2019). However, limited contemporary studies have reported on nurse observations on risk relevant behaviors in patients receiving mandated care.…”
Section: Treatment Change: From a Group To An Individual Levelmentioning
confidence: 99%
“…Less in known about change at a proximal level, thus change in risk relevant behavior during treatment while behavioral change is an important precondition for violence risk prediction. Moreover, assessment of risk relevant behavior is an ongoing process that forensic staff in general but psychiatric nurses in particular undertake on a daily basis (Walker et al, 2019). However, limited contemporary studies have reported on nurse observations on risk relevant behaviors in patients receiving mandated care.…”
Section: Treatment Change: From a Group To An Individual Levelmentioning
confidence: 99%